Association of Being Bullied in School With Suicide Ideation and Planning Among Rural Middle School Adolescents. (November 2014) - Bhatta, Madhav P.; Shakya, Sunita; Jefferis, Eric
ABSTRACT BACKGROUND This study examined the association of ever being bullied in school with suicide ideation (ever thinking about killing oneself) and ever seriously making a plan to kill oneself (suicide planning) among rural middle school adolescents. METHODS Using the US Centers for Disease Control and Prevention's Middle School Youth Risk Behavior Survey instrument, 2 cross‐sectional surveys were conducted among middle school adolescents (N = 1082) in a rural Appalachian county in Ohio in 2009 and 2012. Multivariable logistic regression models assessed the relationship of ever being bullied in school with suicide ideation and planning. RESULTS Overall, a total of 468 participants (43.1%) reported ever being bullied in school, and 22.3% and 13.2% of the adolescents surveyed reported suicide ideation and planning, respectively. In the multivariable analyses, ever being bullied in school was significantly associated with both suicide ideation (odds ratio [OR] = 2.4; 95% confidence interval [CI]: 1.7‐3.5) and planning (OR = 2.5; 95% CI: 1.6‐3.8). CONCLUSIONS The results show a strong association between being bullied in school and suicide ideation and planning among rural middle school adolescents. Prevention of bullying in school as early as in middle school should be a strategy for reducing suicide ideation and planning among adolescents.